Presidential campaigns : from George Washington to George W. Bush - Boller, Paul F. (Oxford University Press, 2004)
"Presidential Campaigns devotes a chapter to each of America's elections, from George Washington's in 1789 to George W. Bush's in 2000, dealing with the candidates, the conventions, the party platforms, the speeches, and the reasons for the victories and defeats on election day. The book contains campaign highlights, too, singling out for special attention the gaffes, surprises, dramatic events, and novel ways of vote-chasing that turned up in each campaign. With a postscript analyzing the major changes in the ways Americans have conducted their campaigns through the years, Presidential Campaigns shows that for all their shortcomings, America's quadrennial races represent a basic feature of the American system and, for better or worse, reveal a great deal about the nature of the American people and their culture."--Jacket.